DEVELOPMENT OF PROBLEM BASED LEARNING PROBLEM BASED MEDIA PICTURE STORY BOOKS IN LEARNING THEMATIC THEME OF MY OBLIGATIONS AND RIGHTS IN CLASS III OF PRIMARY SCHOOL - Oktavia, Venny; Nurhasanah, Nurhasanah (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research is a type of research and development referring to the 4D model consisting of Define, Design, Development and Dissemination. The instrument used to collect data was a questionnaire. Data analysis techniques were descriptive qualitative. The results of the second stage of material expert validation got a percentage of 88%. This percentage included the criteria of "very valid" to be used as a medium in learning activities for grade III of elementary school students with the theme of Kewajiban dan Hakku. Based on the results of media validation, the percentage was 92%. This percentage included the criteria of "very feasible" to be used as a medium in learning activities for grade III of elementary school students with the theme of obligations and rights. Based on the results of the practicality test, the teacher’s response got a percentage of 88%. This percentage included the criteria of "very valid" to be used as a medium in learning activities for grade III elementary school students with the theme of Kewajiban dan Hakku. Linguist validation got a percentage of 90%. Based on the validation results obtained, it can be stated that the picture book media was based on Problem Based Learning on thematic learning on the theme of Kewajiban dan Hakku in grade III of elementary school.